Trypanosoma cruzi Mitochondrial Peroxiredoxin Promotes Infectivity in Macrophages and Attenuates Nifurtimox Toxicity - Specker, Gabriela; Estrada, Damián; Radi, Rafael; Piacenza, Lucía (Frontiers in Cellular and Infection Microbiology, 2022)
Trypanosoma cruzi is the causative agent of Chagas disease which is currently treated by nifurtimox (NFX) and benznidazole (BZ). Nevertheless, the mechanism of action of NFX is not completely established. Herein, we show the protective effects of T. cruzi mitochondrial peroxiredoxin (MPX) in macrophage infections and in response to NFX toxicity. After a 3-day treatment of epimastigotes with NFX, MPX content increased (2.5-fold) with respect to control, and interestingly, an MPX-overexpressing strain was more resistant to the drug. The generation of mitochondrial reactive species and the redox status of the low molecular weight thiols of the parasite were not affected by NFX treatment indicating the absence of oxidative stress in this condition. Since MPX was shown to be protective and overexpressed in drug-challenged parasites, non-classical peroxiredoxin activity was studied. We found that recombinant MPX exhibits holdase activity independently of its redox state and that its overexpression was also observed in temperature-challenged parasites. Moreover, increased holdase activity (2-fold) together with an augmented protease activity (proteasome-related) and an enhancement in ubiquitinylated proteins was found in NFX-treated parasites. These results suggest a protective role of MPX holdase activity toward NFX toxicity. Trypanosoma cruzi has a complex life cycle, part of which involves the invasion of mammalian cells, where parasite replication inside the host occurs. In the early stages of the infection, macrophages recognize and engulf T. cruzi with the generation of reactive oxygen and nitrogen species toward the internalized parasite. Parasites overexpressing MPX produced higher macrophage infection yield compared with wild-type parasites. The relevance of peroxidase vs. holdase activity of MPX during macrophage infections was assessed using conoidin A (CA), a covalent, cell-permeable inhibitor of peroxiredoxin peroxidase activity. Covalent adducts of MPX were detected in CA-treated parasites, which proves its action in vivo. The pretreatment of parasites with CA led to a reduced infection index in macrophages revealing that the peroxidase activity of peroxiredoxin is crucial during this infection process. Our results confirm the importance of peroxidase activity during macrophage infection and provide insights for the relevance of MPX holdase activity in NFX resistance.